Multiple pancreatic metastases of renal cell carcinoma – case report - Hać, Stanisław; Sworczak, Krzysztof; Rzepko, Robert; Śledziński, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2007)
Renal cell carcinoma is the most common renal malignancy. The biology of the disease is characterized by the possibility of late recurrences in unusual localizations. Authors presented pancreatic multiple metastases of renal cell carcinoma 19 years after renal tumor excision.